Malignant extracranial germ cell tumours: A first national report by the South African Children's Cancer Study Group - Hendricks, Marc; Cois, Annibale; Geel, Jennifer; du Plessis, Johan; Bassingthwaighte, Mairi; Naidu, Gita; Rowe, Biance; Büchner, Ané; Omar, Fareed; Thomas, Karla; Uys, Ronelle; Zyl, Anel; et al. (Pediatric blood & cancer, 2022)
Objective To determine the overall survival (OS) and prognostic factors influencing outcomes in children and adolescents with malignant extracranial germ cell tumours (MEGCTs) in preparation for the development of a harmonised national treatment protocol. Methods A retrospective folder review was undertaken at nine South African paediatric oncology units to document patient profiles, tumour and treatment‐related data and outcomes for all children with biopsy‐proven MEGCTs from birth up to and including 16 years of age. Results Between 1 January 2000 and 31 December 2015, 218 patients were diagnosed with MEGCTs. Female sex (hazard ratio [HR] 0.284, p = .037) and higher socio‐economic status (SES) (HR 0.071, p = .039) were associated with a significantly lower risk of death. Advanced clinical stage at diagnosis significantly affected 5‐year OS: stage I: 96%; stage II: 94.3%; stage III: 75.5% (p = .017) and stage IV (60.1%; p < .001). There was a significant association between earlier stage at presentation and higher SES (p = .03). Patients with a serum alpha‐fetoprotein (AFP) level of more than 33,000 ng/ml at diagnosis had significantly poorer outcomes (p = .002). The use of chemotherapy significantly improved survival, irrespective of the regimen used (p < .001). Conclusions The cohort demonstrated a 5‐year OS of 80.3% with an event‐free survival (EFS) of 75.3%. Stage, the use of chemotherapy and an elevated serum AFP level of more than 33,000 ng/ml were independently predictive of outcome. The relationship between SES and outcome is important as the implementation of the new national protocol hopes to standardise care across the socio‐economic divide.